Silane crosslinking of polyethylene: the effects of EVA, ATH and Sb2O3 on properties of the production in continuous grafting of LDPE (eXPRESS Polymer Letters)
In this study, thermal, mechanical and fire retardant properties of silane-crosslinked low-density polyethylene (XLPE) containing ethylene-vinylacetate (EVA) copolymer, alumina trihydrate (ATH) and antimony trioxide (Sb2O3) have been studied. Samples were prepared in a single-screw extruder and the silane type was vinyltrimethoxy silane (VTMOS). Incorporation of ATH and Sb2O3 into polyethylene at sufficiently high loading introduces good fire retardancy expressed by limiting oxygen index (LOI). However, some tensile properties decreased. These limitations could be overcome by silane crosslinking. By incorporation of EVA into XLPE gel content increased and curing time decreased. Differential scanning calorimetric (DSC) analysis indicated the existence of two distinct melting endothermic peaks corresponding to two different crystalline phases. Results from mechanical properties showed that mechanical properties of XLPE/EVA blends improve by increasing EVA content up to 15 wt%.